Reciprocity and dependency in old age : Indian and UK perspectives - Thompson, Sue (International Perspectives on Aging, 2013)
It's the standard picture, and a depressing one: older adults receiving formal care as passive and alienated. Overlooked in this equation is the capacity of dependent elders for giving back - doing for others - and their need to continue finding meaning to their existence which is an essential aspect of improving their lives and care.  Reciprocity and Dependency in Old Age presents an empowering new paradigm for reframing our conception of the lives of elders who are in need of care. Elegantly reasoned and meticulously researched, the book explores the importance of connectedness in later years, and argues that facilitating reciprocity benefits all parties involved - elders, caregivers, and society at large. Reframing dependent care in a more positive light is highlighted as a crucial step toward recognizing older adults' value, thereby improving their self-esteem and promoting their dignity. The importance of promoting change in care systems in order to facilitate the building up of social capital is also addressed.  This important volume: Presents the findings of an extensive research study on reciprocity in later life. Provides phenomenologically and sociologically grounded frameworks for understanding reciprocity in the lives of elders. Gives voice to frequently neglected perspectives on elders' well-being. Relates the study findings to elders' spiritual dimension and aspirations for a future as well as a present and a past. Offers a means of transforming deficit models of old age. Examines the potential for improving the future of eldercare.  With its powerful vision, Reciprocity and Dependency in Old Age is certain to be read and discussed by practitioners, educators and students in a range of fields, including gerontology, sociology, social policy, social work, health and social care, psychology, pastoral care, and by others committed to improving quality of life for older adults.